Analisis Pengelolaan Aset Tetap Sesuai Dengan PSAP No. 07 pada BKPSDM Kota Sukabumi - Verawati Khaniyasti; Ade Sudarma; Sulaeman (Economic Reviews Journal, 2024)
This study was conducted to determine how the management of fixed assets in accordance with PSAP No. 07 at the BKPSDM office of Sukabumi City. This study uses a qualitative method with a descriptive approach. Data collection was obtained from observation, interviews and documentation. Data analysis techniques are done by data reduction, data presentation and conclusion drawing. The results of this study indicate that the management of fixed assets at BKPSDM Kota Sukabumi is in accordance with the provisions of Government Accounting Standards Statement (PSAP) No. 07 covering all categories set out in the standard. The practice of recognizing fixed assets complies with the criteria and provisions of Government Accounting Standard No. 07, including aspects of tangibility, useful life, cost measurement, intended use, and transfer of ownership rights. Measurement of fixed assets is carried out at the time of acquisition using acquisition cost as the basis for valuation and taking into account all related expenses. Depreciation of fixed assets has been carried out in accordance with PSAP No. 07, except for land which is not depreciated. Disclosure of fixed assets in the financial statements has also been in accordance with PSAP No. 07, presenting comprehensive information about fixed assets.